Drug-induced Nephrotoxicity and Medicinal Plants (Iranian Journal of Kidney Diseases, 2017)
Drug-induced nephrotoxicity is one of the most common causes of acute kidney injury. There are various agents that exert nephrotoxic effects through different pathogenic mechanisms. Aminoglycoside antibiotics, chemotherapeutic agents, radiocontrast media, and nonsteroidal anti-inflammatory drugs are among common nephrotoxic agents. In recent years, natural compounds are being increasingly used in the treatment of kidney diseases. Given many reports available on the curative effects of a variety of medicinal plants against drug-associated nephrotoxicity, we aimed to review the protective effects of medicinal plants on certain nephrotoxic drugs.